2017
DOI: 10.1177/0284185117745907
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the maximum standardized uptake value of pre-treatment primary lesions in small-cell lung cancer on 18F-FDG PET/CT: a meta-analysis

Abstract: Background 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG-PET/CT) has been widely used in clinical practice. However, the prognostic value of the pre-treatment standardized uptake value (SUV) for patients with small-cell lung cancer (SCLC) remains controversial. Purpose To investigate the prognostic role of pre-treatment 18F-FDG PET on SCLC patients by meta-analysis. Material and Methods Extensive literature searches of the PubMed, EMBASE, Web of Science, and Cochrane Library … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…A recent meta-analysis demonstrated that the pre-treatment SUV Max in primary lesions can be an important prognostic factor for overall survival (OS) and event-free survival (EFS) in patients with SCLC. [20] According to the recent National Comprehensive Cancer Network (NCCN) guidelines, [21] the PET scan can increase staging accuracy in patients with SCLC, because SCLC is a highly metabolic disease. If limited-stage disease is suspected, a PET/CT scan can be performed to assess for distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis demonstrated that the pre-treatment SUV Max in primary lesions can be an important prognostic factor for overall survival (OS) and event-free survival (EFS) in patients with SCLC. [20] According to the recent National Comprehensive Cancer Network (NCCN) guidelines, [21] the PET scan can increase staging accuracy in patients with SCLC, because SCLC is a highly metabolic disease. If limited-stage disease is suspected, a PET/CT scan can be performed to assess for distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The National Comprehensive Cancer Network guidelines have recommended the application of 18 F-FDG PET/CT for SCLC patients (Johnson 2001 ). SUVmax measured on 18 F-FDG PET/CT is used to quantify FDG uptake of tumor cells; the degree of tumor uptake of 18 F-FDG on PET/CT is shown to be an valuable prognostic gauge in malignant tumors (Bai et al 2017 ; Hsieh et al 2018 ; Hsu et al 2016 ; Kwon et al 2016 ; Lee et al 2015 , 2018 ; Park et al 2014 , 2016 ; Zhu et al 2018 ). While, volumetric parameters such as metabolic tumor volume (MTV) and total lesion glycolysis (TLG) are investigated for independent prognostic parameters in NSCLC and some other cancers (Albano et al 2018 ; Burger et al 2016 ; Hasbek et al 2019 ; Lemarignier et al 2017 ; Tsujikawa et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography-computed tomography (PET/CT) has been widely used in the diagnosis, staging and therapeutic evaluation of various malignancies. [16,17] Also, the prognostic prediction value in PDAC was reported by several researchers. [1820] For resected PDAC patients, 18 F-FDG PET/CT metabolic parameters maximum standardized uptake values (SUVmax), metabolic tumor volume (MTV) and total lesion glycolysis (TLG) were illustrated to strongly correlate with OS and progression-free survival (PFS).…”
Section: Introductionmentioning
confidence: 99%